Time for health a campaign proposal on type 2 diabetes prevention for FIlipino adults ages 24 to 35 working in the business centers of Metro Manila - de los Reyes, Angelo Miguel M.
Diabetes is one of the leading causes of death globally and is increasingly becoming more prevalent in the Philippines due to the Westernization of the Filipino diet, the urbanization of areas and the overdependence on technology that creates sedentary lifestyles ("2nd National Nutrition Summit"; Paz-Pacheco and Jimeno 2, Pingali 3). The disease, based on government statistics, is most prevalent in the middle to upper class Filipinos that reside in urban areas (Tan). Urban professionals working in business centers are identified to be one of the most vulnerable to type 2 diabetes due to the long working hours with very low occupational activity and the frequent consumption of fast food (Chen et al 29-40). Prevention is deemed as the most effective and most cost-efficient solution, especially a national health system that is still evolving (Napiza-Granada, Mela. Personal communication. 2018). This would entail moderating one's diet, being more physically active, and avoiding consumption of alcohol and tobacco products. However, even with the implementation of campaigns by the Department of Health, an upward trend of incidence is still observed. Furthermore, data from a conducted survey have shown that the visual communication materials employed by previous campaigns were not considered engaging or appealing enough to convince the target audience to adopt a healthier behavior. Survey respondents have also stated that one of the major factors that inhibits them from a healthy lifestyle is the lack of time - due to work - to be active and prepare healthier meals.